The Reception of Spinoza’s Theological-Political Treatise in the Islamic Republic of Iran - Sina Mirzaei (Philosophies, 2021)
In the form of a case study and based upon novel material about the reception of Spinoza’s Theological–Political Treatise (TTP) in Iran, this paper studies issues with the interactions among political, theological and philosophical ideas in the reception of Spinoza’s TTP. The paper starts with the first Iranian encounters with Spinoza’s philosophy in the Qajar era in the nineteenth century and then focuses on the reception of the TTP in the period after the 1979 Islamic Revolution. The first translation of the TTP was prepared in the 1990s by Muḥsin Jahāngīrī, but he withheld the manuscript from being published. I discuss the arguments that led him to withhold the publication of his translation; in this context, it will be important to consider the tumultuous religious and political debates, and broader questions as to the legitimacy of political power will also prove relevant. The first doctoral dissertation in Persian about the TTP will be described, followed by a description of a digital translation of the twentieth chapter of the TTP, which was published after the 2009 election protests. The article ends with discussing translator Ali Ferdowsi’s motivation to produce the first complete Persian translation of the TTP, published in Tehran in 2017. In conclusion, it will be discussed to which extent the theocratic political context in the country caused interest in the TTP.